Medical Legal Aspects of Telemedicine in Italy: Application Fields, Professional Liability and Focus on Care Services During the COVID-19 Health Emergency. (December 2020) - Ferorelli, D.; Nardelli, L.; Spagnolo, L.; Corradi, S.; Silvestre, M.; Misceo, F.; Marrone, M.; Zotti, F.; Mandarelli, G.; Solarino, B.; Dell'Erba, A.
Telemedicine services can be classified into the macro-categories of specialist Telemedicine, Tele-health and Tele-assistance. From a regulatory perspective, in Italy, the first provision dedicated to the implementation of Telemedicine services is represented by the Agreement between the Government and the Regions on the document bearing "Telemedicine—National guidelines, " approved by the General Assembly of the Superior Health Council in the session of 10th July 2012 and by the State Regions Conference in the session of 20th February 2014. Scientifically, several studies in the literature state that information and communication technologies have great potential to reduce the costs of health care services in terms of planning and making appropriate decisions that provide timely tools to patients. Another clear benefit is the equity of access to health care. The evolution of telemedicine poses a series of legal problems ranging from the profiles on the subject of authorization and accreditation to those concerning the protection of patient confidentiality, the definition and solution of which, in the absence of specific regulatory provisions, is mainly left to the assessment of compatibility of the practices adopted so far, with the general regulatory framework. In terms of professional liability, it is necessary to first clarify that the telemedicine service is comparable to any diagnostic-therapeutic health service considering that the telemedicine service does not replace the traditional health service, but integrates the latter to improve its effectiveness, efficiency and appropriateness.